Land Uses and Transportation Policies in The Development Of Jakarta - Sidarta, Mochammad (Journal of Regional and City Planning, 1993)
The development of Jakarta since 1965, were guided by a structured plan that are âJakarta Master Plan 1965â1985â and "Jakarta 2005â. Implementation of projects by either central goverment or local goverment in Indonesia, use a uniform system.We have 18 sectors of development project, including agriculture regional development, industry, comunications, which comprises also sectors such as land comunications and tourism.Transportation up to now are goverment functions. Provision of transportation infrastructure become either Central or Local Goverment tasks. Since the real development of an area or a city are carried out and finance by the limited budget of goverment are spend on provision of infrastructures as so that create a favourable climate for the people to develop and build their activities.Â Land use development is subject to provision of infrastructures. On the other hand, activities created by land use development, needed more infrastructures, and all are an unending process.In Jakarta such kind of process were surely happened but interaction between land use development policies and development of transportation, in many cases, are influenced heavily by political will of the goverment, consistency of policies such as planning policies and others non intangable factors.Â A policy on land use development of ribbon development for example (which were much preffered by the investors) are quite different with a centralized centre of activities. These policies reflect on the provision and development of transportation infrastructures. lncosistancy in such land use development policies will give a different impact on the capacity of the provided infrastructures. And that happened time to time with so many reasons. But more importants are that both policies should be integrated and in actualimplementation should be given with neccesary tools for implementation.Without the necessary tools, such as planning regulation, land use determination, taxation, regulation on land etc., that a different impact on the whole development can be expected.